The Role of Profit-Sharing Ratio, Sharia Financial Market Securities, and Covid-19 in Influencing Third Party Funds of Islamic Banking in Indonesia - Qurrota, Saidah; budi sekaringsih, riswanti (Bulletin of Islamic Economics, 2025)
This study aims to analyze the influence of Profit Sharing Ratio (Nisbah), Sharia Money Market Securities (SBPU Syariah), and the Covid-19 pandemic on Islamic banking Third Party Funds (DPK) in Indonesia. The data used is a monthly time series secondary data from January 2018 to December 2023 consisting of 72 observations, obtained from OJK Sharia Banking Statistics. The analysis methods used were multiple linear regression and quadratic functional form regression with the application of STATA. The results of the study show that the variables of Profit Sharing Ratio and Sharia Money Market Securities (SBPU Syariah) have a positive and significant effect on Third Party Funds. However, the relationship between the Ratio and the Third Party Funds is non-linear, where the increase in the ratio to a certain point encourages the growth of the Third Party Fund, but will decrease after passing the optimal point. Meanwhile, the Covid-19 dummy variable also has a positive and significant influence on Third-Party Funds, showing that during the pandemic people tend to increase their deposits in Islamic banking.